2011 49th Annual Allerton Conference on Communication, Control, and Computing (Allerton) 2011
DOI: 10.1109/allerton.2011.6120199
|View full text |Cite
|
Sign up to set email alerts
|

Multi-user two-way deterministic modulo 2 adder channels — When adaptation is useless

Abstract: In two-way channels nodes are both sources and destinations of messages, allowing them to "adapt" or "interact" in the sense that their next channel input may be a function of their past received signals. This "adaptation" and how to best exploit it lies at the heart of two-way communication problems, rendering them particularly complex and challenging. It would be useful to know when adaptation is not beneficial from a capacity perspective. Certain examples exist: it is known that for the pointto-point two-wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 16 publications
0
18
0
Order By: Relevance
“…This path is "blocked" by the partial adaptation assumption, as node 3 could not adapt to carry M 12 . However, it should be pointed out that this is not necessary in general: adaptation in the two-way modulo 2 adder IC is useless [14], but the path is not blocked.…”
Section: Theoremmentioning
confidence: 97%
See 2 more Smart Citations
“…This path is "blocked" by the partial adaptation assumption, as node 3 could not adapt to carry M 12 . However, it should be pointed out that this is not necessary in general: adaptation in the two-way modulo 2 adder IC is useless [14], but the path is not blocked.…”
Section: Theoremmentioning
confidence: 97%
“…In all these channel models only two messages are present and the backwards feedback links, whether perfect, noisy, or interfering still serve only to further rates in the forward direction. The tradeoff between sending new information versus feedback on each of the links is not addressed; the only other example of such a 4-message two-way interference channel besides our prior work [14], [15] is in Section VI of [13], where an example of a linear deterministic scheme in a specific regime is provided.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…where g jk , for j, k ∈ {1, 2, 3, 4} are the complex channel gains. We assume the power constraints E[|X j | 2 ] ≤ P j = 1, j ∈ {1, 2, 3, 4}, and independent, identically distributed complex Gaussian noise Z j ∼ CN (0, 1) at all nodes j ∈ (1,2,3,4), which may be done…”
Section: A Channel Model Definitions and Partial Adaptation Lemmamentioning
confidence: 99%
“…In particular, in [3] we obtained the capacity regions of the deterministic, binary modulo 2 adder models for all three channels, where it was shown that adaptation at the nodes does not increase the capacity regions beyond non-adaptive schemes. In follow-up work in [4] we considered a slightly more general class of deterministic channels: the linear deterministic channels in the spirit of [5].…”
Section: Introductionmentioning
confidence: 99%